Relación entre las expectativas por la carrera docente y el rendimiento académico en los estudiantes de la carrera profesional de educación de la facultad de educación y humanidades - Vargas Huamán, Deivin (2011)
When a student is faced with the fact of choosing a career converge on the emotional structure of his personality a series of motivational elements that test their strength, and by that strength can definitely and steer their interests for a career that gives the satisfactions that require you to search and personal fulfillment. The production of motivated behavior in an individual is fundamental to the way they act. Concretely (Mayor and Tortosa) explain that this behavior has motivated significant features, such as deficiency or decrease in some variable level necessary for the functioning of the body triggers a process that aims to inform the individual that he "knows" you have to carry out any activity that restares the balance in that variable. As a result of that notice, the individual usually experiences some discomfort as typical, it is likely to start motivated behavior designed to eliminate the discomfort and restore balance or level of that variable. Then, the motivation for the race creates expectations on the student becomes part of their personal motivation and interest are made only by or for the pleasure of performing the inherent activities, this characterizes the interest in the race as a motivation type intrinsic since its function appears as a psychological need that drives the student to improve and master the training requirements of the profession that encourages the most difficult goals to achieve. Our research was aimed at finding the possible relationship between expectations for the teaching profession and the academic performance of students in the Faculty of Education and Humanities, School of Education Academic, home Rioja with the aim that, by studying , it has a clear vision of the emotional component of the students as a determinant in their academic performance. The two key instruments for the assessment of the variables considered in the study were: an inventory of expectations for the teaching profession, through which we verified the presence of indicators in its five constituent dimensions, the other instrument was a record of notes to organize the qualifying academic achievement expressed in semi-weighted averages. The general trend of the expectations of students against the teaching profession is positive even with highly significant trends that cuts across both the career of early education and in careers in primary and secondary school career. However, in terms of academic performance as a second variable, we found a set of descriptions of the regular level in all career levels, which show satisfactory performance being not so good student. The real value of the data showed a weak relationship between teaching career expectations of students and their academic performance, consider that there is more than coincidental manifestation of a fact that in reality exists: the presence of multiple factors or variables affecting academic. performance. Without that motivation is the variable with the highest incidence, its presence is always evident and constitutes an important aspect in the spectrum of mental phenomena of human motivation associated with student development.